2022
DOI: 10.1186/s12967-022-03536-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA RP3-525N10.2-NFKB1-PROS1 triplet-mediated low PROS1 expression is an onco-immunological biomarker in low-grade gliomas: a pan-cancer analysis with experimental verification

Abstract: Background Glioma is the most common cancer in the central nervous system, and low grade gliomas are notorious for many types of tumors and heterogeneity. PROS1 not only plays an important role in the blood coagulation system, and recent studies have found that it was correlated with the development of tumors, especially related to tumor immune infiltration. However, the study of underlying role and mechanism of PROS1 in gliomas, especially in low-grade gliomas, is almost absent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Glioma is called a “cold” tumor with poorly T cell-exhausted and less responsive to immune checkpoints ( 44 ). However, some studies have shown that targeted PROS1 might decrease immune checkpoint gene expression and increase the efficacy of immunotherapy ( 45 ). According to us, the expression of PROS1 is significantly related to marker genes of T cell exhaustion (PD-L1, HAVCR2, and CTLA4), and immunosuppressive immune cells (TAMs, MDSC, and Treg) ( Figures 6D, E ).…”
Section: Discussionmentioning
confidence: 99%
“…Glioma is called a “cold” tumor with poorly T cell-exhausted and less responsive to immune checkpoints ( 44 ). However, some studies have shown that targeted PROS1 might decrease immune checkpoint gene expression and increase the efficacy of immunotherapy ( 45 ). According to us, the expression of PROS1 is significantly related to marker genes of T cell exhaustion (PD-L1, HAVCR2, and CTLA4), and immunosuppressive immune cells (TAMs, MDSC, and Treg) ( Figures 6D, E ).…”
Section: Discussionmentioning
confidence: 99%
“…PROS1 , a vital blood coagulation gene, was considered to promote the glioma immunosuppressive microenvironment ( 80 ). In addition, another study showed PROS1 was enriched in complement activation in LGG, indicating the critical role of CCC in the progression of LGG ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assay complies with the protocol described in a previous article [ 16 ]. Short hairpin RNA (shRNA) against EREG (shEREG) and a negative control shRNA (sh NC) were designed and synthesized by GeneCreate (Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%